Ni (II) and Cd (II) Complexes Derivatives from Heterocyclic Schiff Base; Synthesis, Spectroscopic and Biological Studies - Fawzi Y. Waddai (Journal of Global Pharma Technology, 2018)
Ni and Cd complexes of new Schiff base derived from 5-Amino-2-phenyl-2,4-dihydro-pyrazol-3-one with 4-chlorobenzalaldehyde (A) , 2-Hydroxy-benzalaldehyde (B) and 4-Hydroxy-benzaldehyde (C) have been prepared and characterized by elemental analysis ,molar conductivity measurements, FTIR, UV-vis, 1HNMR, mass spectrometer and magnetic susceptibility. Analytical data revealed that six complexes were a distorted tetrahedral geometry and exhibited (1:1) metal: ligand ratio. The biological activity for the three ligands and its complexes were studied.